Analisis Faktor Eksploratori Layanan @syariahmandiri - Arissetyanto Nugroho (Jurnal Ekonomi, 2018)
The bank competition in Indonesia is high, conventional banks and sharia banks strive to improve competitiveness and gain positioning in the minds of the consumers. Previous research conducted by @bankmandiri compared to @syariahmandiri in 2015 gives the managerial implication that Syariah bank's Twitter is not as active as a conventional bank. @bankmandiri frequency compared to @syariahmandiri is different. The variety of the service proposition @syariahmandiri is fewer than the variety of service proposition @bankmandiri. The follow-up research is conducted by using the @syariahmandiri tweets data from January to July 2016. The data was processed with the Provalis Research software, to obtain descriptive frequencies, hashtags, mentions and extracted name entities, cluster analysis, and to obtain the service proposition of @syariahmandiri. The results show a robust development @syariahmandiri twitter activities, an increasing number of tweet frequencies and varieties of service proposition compare with January to December 2015 dataset.